Heart failure with preserved ejection fraction is the most frequent but commonly overlooked phenotype in patients on chronic hemodialysis - Malik, Jan; Valerianova, Anna; Pesickova, Satu Sinikka; Michalickova, Kristyna; Hladinova, Zuzana; Hruskova, Zdenka; Bednarova, Vladimira; Rocinova, Katarina; Tothova, Monika; Kratochvilova, Marketa; Kaiserova, Lucie; Buryskova Salajova, Kristina; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Heart failure (HF) is a serious complication of end-stage kidney disease (ESKD). However, most data come from retrospective studies that included patients at time of hemodialysis initiation, when overhydration is frequent. The primary aim of this study was to analyze the prevalence of HFand its phenotypes. Secondary aims were: 1. To describe the potential of NTproBNP for HF diagnosis in ESKD patients on hemodialysis; 2. To analyze the frequency of abnormal left ventricular geometry; 3. To describe differences between various HF phenotypes in this population. Methods: We included all patients on chronic hemodialysis for at least 3 months from 5 hemodialysis units that were willing to participate, had no living kidney transplant donor and their life expectancy was longer than 6 months. Echocardiography with hemodynamic calculations, dialysis arteriovenous fistula flow volume calculation, bio-impedance and basic lab analysis were performed in conditions of clinical stability. Results: 214 patients aged 66.4±14.6 years were included. HF was diagnosed in 57% of them. Among patients with HF, HFpEF occurred in 35%, while HFrEF only in 7%, HFmrEF 7% and high-output HF in 9%). Patients with HFpEF differed from patients with no HF significantly in the following: they were older (62±14 vs. 70±14, p=0.002), had higher left ventricular mass index [96(36) vs. 108(45), p=0.015], higher left atrial index [33(12) vs. 44(16), p<0.0001], higher estimated central venous pressure [5(4) vs. 6(8), p=0.004] and pulmonary arterial systolic pressure [31(9) vs. 40(23), p=0.006], but slightly lower tricuspid annular plane systolic excursion: 22±5 vs. 24±5, p=0.04. NTproBNP had low sensitivity and specificity for diagnosing HF or HFpEF: with the use of the cut-off value of 8296 ng/L, the sensitivity of HF diagnosis was only 52% while the specificity was 79%. However, NTproBNP levels were significantly related to echocardiographic variables, especially to the indexed left atrial volume (R = 0.56, p<10-5) and to the systolic pulmonary arterial pressure (R = 0.50, p<10-5). Conclusions: HFpEF was the most common HF phenotype in patients on chronic hemodialysis. HFpEF patients were older, had typical echocardiographical changes, but also higher hydration that mirrored increased filling pressures of both ventricles than patients without HF.